2016
DOI: 10.1093/nutrit/nuw020
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the nutrition transition for vitamin D intake and status in Aboriginal groups in the Canadian Arctic

Abstract: Aboriginal Canadians have low intakes of vitamin D and are shifting away from consumption of traditional foods. Higher body mass index, skin pigmentation, and geographic latitude of residence further predispose Canadian Aboriginal populations to low vitamin D status. Low vitamin D status could compromise bone health and other health outcomes. Studies assessing vitamin D status of different Aboriginal groups are limited. The aim of this review is to examine the literature on vitamin D status and intakes of Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Multivariable logistic regression models in males and females to assess ethnic differences in the prevalence of serum 25 Table 4). However, after adjustment for additional variables (age group, month of blood draw, sunbathing holiday in the past month, use of supplements other than cod-liver oil and vitamin D intake), the association was no longer significant (model 2 in Table 4).…”
Section: Public Health Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable logistic regression models in males and females to assess ethnic differences in the prevalence of serum 25 Table 4). However, after adjustment for additional variables (age group, month of blood draw, sunbathing holiday in the past month, use of supplements other than cod-liver oil and vitamin D intake), the association was no longer significant (model 2 in Table 4).…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Cod (Gadus mothua L.) liver is consumed during the winter months (January-March/ April) and saithe (Pollachius virens) liver is consumed from late summer until autumn (July-September/October). Reduction of consumption of traditional foods has been shown to be associated with insufficient nutrient intakes and a decrease in circulating 25(OH)D concentration among certain Indigenous populations in the Arctic (25,26) .…”
mentioning
confidence: 99%
“…Food insecurity and reduced CF consumption may combine to produce dietary inadequacies and nutrient deficiencies across Inuit communities (53,(107)(108)(109)(110)(111)(112)(113)(114)(115)(116) . Studies reporting on dietary adequacy suggested that consumption of micronutrients (e.g.…”
Section: Possible Impacts Of the Dietary Transition On Health Outcomesmentioning
confidence: 99%
“…These studies show a predominance of low serum vitamin D levels, that is, insufficiency (<75 nmol/L or 30 ng/ml), or even deficiency (<25 nmol/L or 10 ng/ml) (Andersen et al, 2018; El Hayek Fares & Weiler, 2016; Hagenau et al, 2009; Tse, Weiler, & Kovesi, 2016). Nielsen et al (2014) and El Hayek Fares and Weiler (2016) also observed a decline in serum vitamin D status among Inuit over time, indicating the impacts of replacing the traditional diet (Nielsen et al, 2014). More recently, studies corroborate a high prevalence of vitamin D insufficiency/deficiency in Inuits, highlighting a correlation with dietary habits (Courraud et al, 2020).…”
Section: Native Americans: Skin Color and Vitamin Dmentioning
confidence: 99%